Demonstration of a Herpes Group Virus in Cultures of Peripheral Leukocytes from Patients with Infectious Mononucleosis - Diehl, Volker (1968)
Cultures were initiated with peripheral leukocytes from individuals: (i) in the acute stage of infectious mononucleosis (IM); (ii) with past histories of IM; and (iii) without histories of IM and without antibodies to EB virus (EBV). In confirmation of other reports, the first group of cultures developed readily and rapidly into lines of blastoid cells. Cellular replication commenced in 24 of 25 attempts within 17 to 28 days, regardless of the technique employed; i.e., initial seeding of the leukocytes with or without addition of phytohemagglutinin onto monolayers of human diploid cells (WI-38) or direct establishment of suspension cultures. EBV was detected in all cultures by immunofluorescence and also by electron microscopy when tested. Furthermore, the nine cultures which were examined cytogenetically revealed the C-group (#10) chromosomal marker previously found in cultured Burkitt tumor cells. These findings supported the earlier conclusion that EBV is related to, if not identical with, the causative agent of IM. Cultures of the second group commenced growth only within 30 to 60 days in five of seven attempts, depending apparently upon the early presence of WI-38 cells. These cultures also revealed the presence of EBV and, in the three examined, the C-group chromosomal marker. Leukocytes of the third group, seeded onto WI-38 monolayers, failed to become established in four attempts. The possible implications of these findings are discussed.